Gender differences in commuting behavior: Women's greater sensitivity - Olmo-Sánchez, María Isabel; Maeso-González, Elvira (Elsevier, 2016)
Women's greater sensitivity to changes in their environment is one of the most distinguishing features between both genders. This article raises women's greater sensitivity to the different variables which influence their commuting modal choice. In order to do this, gender gaps detected in the choice of means of transport in commuting trips with respect to the decision factors such as age, education level, driver's license, private transport access; location, household size and net income, are quantified. The results show a greater female sensitivity to the different variables that affect their modal choice, which helps to better understand the different mobility patterns and it is useful for planning measures favoring sustainable mobility policies and equity.
Keywords: Transporte; Mujeres; Commuting; Inequality; Gender; Modal choice; Transport policy